The IPGA1‐ANGUSTIFOLIA module regulates microtubule organisation and pavement cell shape in Arabidopsis. Issue 4 (1st September 2022) - Chen, Binqing; Dang, Xie; Bai, Wenting; Liu, Min; Li, Ying; Zhu, Lilan; Yang, Yanqiu; Yu, Peihang; Ren, Huibo; Huang, Dingquan; Pan, Xue; Wang, Haifeng; et al.
Summary: Plant cells continuously experience mechanical stress resulting from the cell wall that bears internal turgor pressure. Cortical microtubules align with the predicted maximal tensile stress direction to guide cellulose biosynthesis and therefore results in cell wall reinforcement. We have previously identified Increased Petal Growth Anisotropy (IPGA1) as a putative microtubule‐associated protein in Arabidopsis, but the function of IPGA1 remains unclear. Here, using the Arabidopsis cotyledon pavement cell as a model, we demonstrated that IPGA1 forms protein granules and interacts with ANGUSTIFOLIA (AN) to cooperatively regulate microtubule organisation in response to stress. Application of mechanical perturbations, such as cell ablation, led to microtubule reorganisation into aligned arrays in wild‐type cells. This microtubule response to stress was enhanced in the IPGA1 loss‐of‐function mutant. Mechanical perturbations promoted the formation of IPGA1 granules on microtubules. We further showed that IPGA1 physically interacted with AN both in vitro and on microtubules. The ipga1 mutant alleles exhibited reduced interdigitated growth of pavement cells, with smooth shape. IPGA1 and AN had a genetic interaction in regulating pavement cell shape. Furthermore, IPGA1 genetically and physically interacted with the microtubule‐severing enzyme KATANIN. We propose that the IPGA1‐AN module regulates microtubule organisation and pavement cell shape.